Maternal and Neonatal Outcomes after Planned or Emergency Delivery for Placenta Accreta Spectrum - Sajid, Simab; Nasim, Noreen (Biological and Clinical Sciences Research Journal, 2025)
For the mother, placenta accreta spectrum is a fatal disorder that frequently causes significant blood loss. So, proper management and care are vital to prevent adverse outcomes. Objective: This study aimed to determine the Maternal and Neonatal Outcomes after Planned or Emergency Delivery for Placenta Accreta Spectrum. Methodology: The current cross-sectional descriptive Study was conducted at the Department of Gynecology and Obstetrics, Sheikh Zayed Hospital and Medical College, Rahim Yar Khan, over 6 months. Total 30 women fulfilling the inclusion criteria from the in-patient department of obstetrics and gynecology, SZH RYK were included in the study. Depending on delivery, planned or emergency caesarean delivery, the women were divided into two groups and were followed up for the Maternal & neonatal Outcome. Data were entered into and analyzed using SPSS-24. Results: 30 women with Placenta accreta spectrum were included in the current study. Among them 20(66.6) underwent planned and 10(33.33%) emergency caesarean delivery. The basic maternal characteristics were not significantly different between the two groups; however, the women who had emergency caesarean delivery had a high parity and a lower BMI (P ˂0.05). The group that had an emergency delivery had a considerably larger percentage of women who experienced antepartum haemorrhage (50% P <.001). The median gestational ages at which emergency deliveries occurred were noticeably lower (value of p less than 0.001). Nonetheless, women having an emergency delivery had a greater risk of maternal ICU admissions (value of P.02). We compared neonatal outcome in both groups the admission to intensive care unit in Emergency delivery was higher (48%) as compared to planned delivery (15%) (P value <0.001) Conclusion: Our study concluded that emergency deliveries did not result in higher rates of maternal morbidity, transfusions, or blood loss. Antenatal haemorrhage was the single biggest risk factor for emergency delivery. Emergency delivery increased the risk of maternal and neonatal ICU admissions.